Influence of organosulfur connections on hygroscopicity of transformer oil and its electric characteristics - L. R. Gaynullina; V. P. Tutubalinа (Известия высших учебных заведений: Проблемы энергетики)
The dependency of dissolution of water in oil fraction from temperature and the number of organosulfurcompounds on the usage of model mixtures was studied. It is found, that the increase of concentration of organosulfurcompounds in model mixtures with high temperatures and electric field strength promotes the grouth of water solubility in them. Experimental researches have also shown that increase in concentration of organosulfurcompoundsand hygroscopicity of oil in conditions of his operation in power transformers is followed by growth of dielectric losses and decrease in electrical durability of oil.